Le développement constitutionnel de l’Ethiopie durant la période révolutionnaire (1974–1991) - Scholler, Heinrich (Aethiopica, 2000)
The legal development of the Ethiopian Revolution (1974–91) is characterised by three different phases equivalent to different levels or developments of the Ethiopian Revolution. A provisional framework was given by the proclamations no. 1 and 2 of 1974. Only in 1987 the so-called Mengistu-Constitution was adopted and seemed to give legal stability to the country. The idea of revolutionary change developed and altered within three phases: The first phase, the French phase, tried to implement so-called “Revolutionary Justice”, the second Chinese phase marked by a red-terror campaign tried to destroy all existing legal structures, while the third phase, a Soviet phase, tried to establish Soviet or Marxist rule by Socialist laws. The article explains the organisation of the Ethiopian State as a result of the Ethiopian Constitution of 1987. The high concentration of all government functions including the judiciary and the parliament (Shengo) is explained. The article does not limit itself to the interpretation and analysis of the new legal documents and instruments and their functions, but tries to interrelate the new legal structures with the corresponding socio-political power process.